VALIDATION OF INSTRUMENT ON MORAL ENGAGEMENT AND DISENGAGEMENT OF TEACHERS IN THE FACE OF BULLYING AT SCHOOL - Paulino Tognetta, Luciene Regina [UNESP]; Aviles Martinez, Jose Maria; Carneiro Goncalves, Catarina; Andrade, Fernando; Boni, Larissa Di Genova [UNESP]; Pupin Santos, Natalia Cristina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
Although bullying occurs in parental relationships, its prevention and overcoming in school demand the intervention of teachers, who need to be able to bring students to the awareness of the moral content at stake in a situation of victimization: this requires teachers to know about values involved in this violence, sensitizing themselves to it. However, studies show that many teachers blame targets for situations of mistreatment or displace the responsibility of intervention for families: they use moral disengagement through which they reduce or refute the problem, making it impossible to overcome it. Thus, we aim to validate a research instrument capable of identifying the most recurrent forms of Disengagement or Moral Engagement manifested by teachers. After extensive review of the literature, two stories were developed characterizing situations involving typical and provocative target, followed by 14 evaluative items appropriate to the eight forms of Moral Disengagement defined by Bandura and three forms of Moral Engagement constructed for this research. After the Principal Components Analysis, the instrument was applied to a sample of 921 teachers from Brazilian and Spanish schools. The results demonstrated the acceptance of the proposed theoretical model, significant factorial loads in the different factors and adequate trustworthiness of the instrument.
Keywords: Validation of Instrument; Moral engagement and disengagements; Teacher; Bullying